Bacterial Translocation – Impact on the Adipocyte Compartment - Kruis, Tassilo; Batra, Arvind; Siegmund, Britta (Frontiers in Immunology, 2014)
Over the last decade it became broadly recognized that adipokines and thus the fat tissue compartment exert a regulatory function on the immune system. Our own group described the pro-inflammatory function of the adipokine leptin within intestinal inflammation in a variety of animal models. Following-up on this initial work, the aim was to reveal stimuli and mechanisms involved in the activation of the fat tissue compartment and the subsequent release of adipokines and other mediators paralleled by the infiltration of immune cells. This review will summarize the current literature on the possible role of the mesenteric fat tissue in intestinal inflammation with a focus on Crohn’s disease. Crohn’s disease is of particular interest in this context since the transmural intestinal inflammation has been associated with a characteristic hypertrophy of the mesenteric fat, a phenomenon called “creeping fat”. The review will address three consecutive questions: i) What is inducing adipocyte activation, ii) which factors are released after activation and what are the consequences for the local fat tissue compartment and infiltrating cells; iii) do the answers generated before allow for an explanation of the role of the mesenteric fat tissue within intestinal inflammation? With this review we will provide a working model indicating a close interaction in between bacterial translocation, activation of the adipocytes and subsequent direction of the infiltrating immune cells. In summary, the models system mesenteric fat indicates a unique way how adipocytes can directly interact with the immune system.